1998
DOI: 10.1021/tx9701384
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic and Methylated Arsenic Compounds Induce Cell Death in Murine Macrophages via Different Mechanisms

Abstract: We demonstrate in this study the cytotoxic effects of inorganic arsenicals, arsenite and arsenate, and organic arsenic compounds, monomethylarsonic acid (MAA), dimethylarsinic acid (DMAA), and trimethylarsine oxide (TMAO), which are metabolites of inorganic arsenicals in human bodies, using murine macrophages in vitro. Inorganic arsenicals, both arsenite and arsenate, are strongly toxic to macrophages, and the concentration that decreased the number of surviving cells to 50% of that in untreated controls (IC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…Sengupta and Bishayi (2002) revealed that arsenic significantly decreased murine splenocyte phagocytic activity. Sakurai et al (1998) reported that arsenite (as sodium arsenite, NaAsO 2 ) at a level of 5 ”M induced apoptosis in murine macrophages in vitro. Fulda and Debatin (2006) suggested that NaAsO 2 may in fact have been inducing this apoptosis by activating an "intrinsic" mitochondrial pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Sengupta and Bishayi (2002) revealed that arsenic significantly decreased murine splenocyte phagocytic activity. Sakurai et al (1998) reported that arsenite (as sodium arsenite, NaAsO 2 ) at a level of 5 ”M induced apoptosis in murine macrophages in vitro. Fulda and Debatin (2006) suggested that NaAsO 2 may in fact have been inducing this apoptosis by activating an "intrinsic" mitochondrial pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It has been generally believed that methylation of inorganic arsenic is a detoxification mechanism [20,21]. Most mammals are able to methylate inorganic arsenic to methylarsonic acid (MMA V ) and dimethylarsinic acid (DMA V ).…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy study revealed that exposure to sodium arsenite caused alteration in the cytoskeleton, Golgi apparatus, mitochondria and perinuclear membrane of the T lymphocytes which ultimately changed intracellular secretion of proteins including IL-2 that might lead to an impaired proliferation of the cells when stimulated with PHA. It has been reported that both arsenite and arsenate are strongly toxic to macrophages and able to decrease the number of surviving cells to 50% at a concentration of 5 or 500 ”M, respectively [16].…”
Section: Introductionmentioning
confidence: 99%